2022
DOI: 10.1128/mbio.03528-21
|View full text |Cite
|
Sign up to set email alerts
|

Human Respiratory Syncytial Virus NS2 Protein Induces Autophagy by Modulating Beclin1 Protein Stabilization and ISGylation

Abstract: Understanding host-virus interactions is essential for the development of effective interventions against respiratory syncytial virus (RSV), a paramyxovirus that is a leading cause of viral pneumonia in infants. RSV induces autophagy following infection, although the viral factors involved in this mechanism are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
1
15
1
Order By: Relevance
“…These findings were further consolidated in recent reports, which identified Respiratory syncytial virus (RSV) NS2 as an antagonist of this pathway. NS2 was found to promote pro-viral autophagy by stabilising Beclin1 and preventing its ISGylation [50]. These data on the negative regulation of autophagy are in line with previous studies on IFNβ-induced ISGylation of Trim21.…”
Section: Regulation Of Autophagysupporting
confidence: 90%
“…These findings were further consolidated in recent reports, which identified Respiratory syncytial virus (RSV) NS2 as an antagonist of this pathway. NS2 was found to promote pro-viral autophagy by stabilising Beclin1 and preventing its ISGylation [50]. These data on the negative regulation of autophagy are in line with previous studies on IFNβ-induced ISGylation of Trim21.…”
Section: Regulation Of Autophagysupporting
confidence: 90%
“…However, the alteration of Beclin 1 protein status along with its localization in parasite containing compartment throughout Leishmania infection in infected macrophages is certainly a new finding. Previously, respiratory syncytial virus (RSV) was found to induce Beclin 1 protein level by inhibiting its degradation to drive enhanced autophagy (Chiok et al, 2022). In fact, increased phosphorylation of Beclin 1 at early time point has been reported during L. donovani infection (Pitale et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the deletion of ISG15 leads to impaired recruitment of p62, NDP52, and LC3 in parasitophorous vacuoles (PV), resulting in interferon-induced autophagy damage. And ISGylation can further inhibit autophagy by reducing the stability of the proautophagy mediator Beclin1 to inhibit its activity [ 56 , 61 , 62 ] ( Figure 3 ).…”
Section: Isgylation In Cancermentioning
confidence: 99%
“…In addition, Xi et al demonstrated that the cancer-promoting effect of USP18 may be achieved through the control of fatty acid metabolism in lung cancer [ 94 ] ( Figure 6 ). Notably, some other studies have shown that USP18 has a strong tumor-promoting effect, indicating that USP18 functions through other important pathways besides de-ISGylase [ 62 , 78 ].…”
Section: Isgylation In Cancermentioning
confidence: 99%